2019
DOI: 10.1007/s00204-019-02460-3
|View full text |Cite
|
Sign up to set email alerts
|

Feeding of deoxynivalenol increases the intestinal paracellular permeability of broiler chickens

Abstract: In recent years, the deleterious effects attributed to mycotoxins, in particular on the intestine, faced increased attention and it was shown that deoxynivalenol (DON) causes adverse effects on gut health. In this context, it has been repeatedly reported that DON can alter the intestinal morphology, disrupt the intestinal barrier and reduce nutrient absorption. The underlying mechanism of a compromised intestinal barrier caused by DON in chickens has yet to be illustrated. Although, DON is rapidly absorbed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 48 publications
7
33
2
Order By: Relevance
“…Notwithstanding, the results reported to date are consistent with the results obtained in the current study. Broiler chicken exposed to 1-5 mg/kg DON experienced significant reduction in body weight and feed intake from Days 17 to 34 [39][40][41][42]. Similarly, Keçi et al [43] reported a decreased body weight gain (up to 6%) in broilers fed DON-contaminated diet.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Notwithstanding, the results reported to date are consistent with the results obtained in the current study. Broiler chicken exposed to 1-5 mg/kg DON experienced significant reduction in body weight and feed intake from Days 17 to 34 [39][40][41][42]. Similarly, Keçi et al [43] reported a decreased body weight gain (up to 6%) in broilers fed DON-contaminated diet.…”
Section: Discussionmentioning
confidence: 89%
“…Consequently, intestinal toxicity of mycotoxins has attracted a lot of scientific interest [ 45 ]. Several researchers have reported an increased paracellular intestinal permeability and translocation of enteric microorganism ( Escherichia coli and Clostridium perfringen ) to the liver and spleen as well as alteration of corticosterone level, intestinal mucus layer and intestinal epithelial antioxidative mechanisms, when birds were exposed to DON and FBs at levels below EU guidance values [ 38 , 42 , 46 , 47 ]. Although broilers intestines were not investigated in this study, we suggest that the reduced feed efficiencies in Trials 1, 2, 8, 9, 14 and 15 may be due to deleterious effects of identified mycotoxins on intestinal mucosa structures and functions.…”
Section: Discussionmentioning
confidence: 99%
“…Both, mycotoxin contamination of feed and C. jejuni prevalence in broilers have an increasing global health and economic impact on poultry production. The Fusarium mycotoxin DON is a ubiquitous mycotoxin with negative effects on the growth performance of broiler chickens (26,27). As an inhibitor of protein synthesis DON mainly affects cells with a high-protein turnover, such as intestinal epithelial and immune cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, during the course of the experiment, 0.6-mL samples were taken from the serosal compartment (cold side) at defined time intervals (every 30-min). Manipulation of Ussing chambers and experimental procedures were performed as described by Awad et al (26). Finally, after addition of a liquid scintillation fluid to all samples up to 5 mL, the presence of radioisotope in the samples was measured by a liquid scintillation counter (Aquasafe 300 Plus, Zinsser Analytic, Maidenhead, UK).…”
Section: Determination Of Paracellular Permeability Applying Ussing Cmentioning
confidence: 99%
“…Chen et al suggested that nontoxic OTA (4 μM) could promote DON-induced (4 μM) intestinal barrier dysfunction in IPEC-J2 cells ( Ying et al, 2019 ). Wageha et al have found that DON (5 and 10 mg/kg feed) could facilitate the translocation of enteric microorganisms such as E. coli to extra-intestinal organs in broiler chickens ( Awad et al, 2019 ). However, the interaction and its mechanism between germ and DON are still unclear.…”
Section: Discussionmentioning
confidence: 99%